(untitled) (Revista Contexto & Saúde, 2025)
Objectives: To describe the process of creating a video channel with evidence of validity as an educational technology to promote self-care and prevention of diabetic foot as a complication of living with diabetes mellitus. Method: Methodological study, developed through data collection in the literature and with the target audience; construction of the video script with chordel literature and video chordel; validation of the material through validation by judges (specialists in the fields of health and chordel) and udability test with the target audience (people living with diabetes in primary health care). Data were analysed descriptively. Results: The content and appearance of the video chordel was validated, with a content validity coefficient of 1.0; with 100% agreement between items; considered adequate for the evaluation of educational material and with the best possible usability in terms of applicability to the target audience. Conclusion: The Video Chordel was validated in all domains evaluated and can be used by people with diabetes to promote self-care and prevention of diabetic foot.